Modelling geospatial distributions of the triatomine vectors of Trypanosoma cruzi in Latin America - Bender, Andreas; Python, Andre; Lindsay, Steve W.; Golding, Nick; Moyes, Catherine L. (PLOS Neglected Tropical Diseases, 2020)
Author summary The Pan American Health Organisation’s Strategy and Plan of Action for Chagas Disease Prevention, Control and Care highlights the importance of eliminating those triatomine vector species that colonise homes, and has had great success in many locations. Since indoor residual spraying campaigns have targeted these species, their importance relative to other vectors has diminished and their geographical distributions may also have changed. It is now vital to consider the full community of vector species, including previously dominant vectors as well as secondary or minor vector species, in order to target residual transmission to humans. Our aim was to define the geographical distributions of the most commonly reported triatomine species in the Chagas endemic region from northern Argentina and Chile to the southern United States of America. We extracted reports of triatomine vector species observed at specific locations from a public database and we used a geostatistical model to generate fine-scale predictive maps for thirty triatomine vector species. Data quality and data availability issues necessitate careful interpretation of the results, so (un)certainty intervals are presented alongside each map. We also present these maps alongside a summary of the published evidence for key indicators related to the capacity of each species to transmit the Chagas parasite to humans. This evidence shows that most of the 30 species that we have mapped pose a potential threat to human populations.